COMPARATIVE EFFECTS OF TBLT ON EFL LEARNERS’ SPEAKING FLUENCY, ACCURACY, AND COMPLEXITY - Juraeva Iroda Akhmedovna; Xayrullayeva Sugdiyona (Modern American Journals, 2025)
This study investigates the comparative effectiveness of Task-Based Language Teaching (TBLT) and traditional grammar-focused instruction in measuring EFL speaking performance. A controlled experiment was conducted on 150 university students, who were divided into TBLT experimental (n = 75) and traditional control (n = 75) groups over a 12-week period. Fluency (speech rate, hesitation patterns), accuracy (grammatical errors, self-corrections), and complexity (syntactic structures, lexical variety) were measured in the speech assessment. TBLT participants showed significant improvements: fluency increased by 38% compared to 14% in the control group, accuracy increased by 31% compared to 16%, and complexity increased by 42% compared to 19%. Statistical analysis revealed large effect sizes (d = 1.15-1.84) supporting the implementation of TBLT. The results indicate the high effectiveness of TBLT in developing balanced speech across all performance measures. The findings support the use of TBLT to enhance broad communicative competence in EFL learning contexts that require authentic speaking skills.
Keywords: Task-based language teaching, English speaking ability, fluency, grammatical accuracy, syntactic complexity, communicative competence